Volume and velocity changes at Mittivakkat Gletscher, southeast Greenland - S. H. Mernild; N. T. Knudsen; M. J. Hoffman; J. C. Yde; Edward Hanna; W. H. Lipscomb; J. K. Malmros; R. S. Fausto (2013)
We document changes for Mittivakkat Gletscher, the peripheral glacier in Greenland with the longest field-based observed mass-balance and surface velocity time series. Between 1986 and 2011, this glacier changed by -15 in mean ice thickness and -30 in volume. We attribute these changes to summer warming and lower winter snow accumulation. Vertical strain compensated for â?¼60 of the elevation change due to surface mass balance (SMB) in the lower part, and â?¼25 in the upper part. The annual mean ice surface velocity changed by -30, which can be fully explained by the dynamic effect of ice thinning, within uncertainty. Mittivakkat Gletscher summer surface velocities were on average 50-60 above winter background values, and up to 160 higher during peak velocity events. Peak velocity events were accompanied by uplift of a few centimeters.